MODERN TECHNOLOGIES AND DIAGNOSTICS IN TREATMENT OF NEUROENDOCRINE TUMORS OF THE PANCREAS - N. A. Maistrenko; P. N. Romashchenko; M. V. Lysanyuk (Вестник хирургии имени И.И. Грекова, 2015)
The article presents the results of investigation and treatment of 124 patients with neuroendocrine tumors of the pancreas (NET P): insulinima (68 cases), gastrinoma (43 cases), rare forms of tumor (13 patients). It was stated that clinical manifestations of NET P resembled the signs of neurological and gastroenterological diseases. Thus, the terms of detection would be prolonged during pre-admission stage and this validated the reasonability of well-timed application of current laboratory methods of diagnostics. An appropriate clinic neuroendocrine syndrome could be confirmed in 93-96% of patients. The authors showed that available diagnostic technique of NET P were the helical computer tomography and endoscopic ultrasound study with sensitivity 75% and 91%, respectively. It was rational to complete study with the data of intraoperative sonography for final tumor localization and its assessment in relation to the connection with pancreas duct and vessels. At the same time, it could be used in case of suspicion to multiple neoplasia. Angiography in combination with arterial-stimulated blood sampling from the hepatic vein and positron emission tomography with 18-fluorodeoxyglucose were the additional methods of diagnostics concerning the main forms of limited hyperinsulinism and generalized forms of NET P. Immunohistochemical study of removed pancreas tumor was the main method of morphological verification of the diagnosis and it’s used to develop the further strategy of postoperative treatment for patients. The surgical method of treatment of patients with NET P allowed elimination of clinical laboratory manifestations of neuroendocrine syndrome and getting general cumulative 5-year survival (69,3±4,7%) of radically operated patients.